The effect of canine therapy on the development of social and emotional areas in children with learning disabilities in school age (Training and Practice : Journal of Educational Sciences, 2020)
The goal of our research is to investigate the impact of canine therapy on the development of children with learning disabilities, with special regard to social and emotional competence. The research question was: to what extent does intensive animal-assisted therapy influence the behaviour of the pupils enrolled in the sample, and can the long-term effects of the therapy be demonstrated and justified? To explore the longitudinal study over six months, a qualitative and quantitative test method was used. As a research tool, we used the Conners Questionnaire on Child Behaviour, which was revealed by descriptive and mathematical statistical analysis. Owing to the multi-focus study, the positive effects of canine therapy were confirmed from several sides. Based on the results we can prove that the canine therapy positively and lastingly influenced the behaviour of the examined children, which showed a positive change in several areas.